NEUROMYELITIS OPTICA IN SOUTH WALES AND THE SOUTH WEST OF ENGLAND. (29th November 2012) - Luppe, S; Harding, KA; Cossburn, M; Ingram, G; Palace, J; Kitley, J; Leite, MI; Jacob, A; Robertson, NP
Abstract : Objectives: To study disease frequency, clinical disease course and relapse rate, in a population-based cohort of patients with NMO and to examine currently employed treatment strategies. Methods: Patients were identified from seven neurology departments in S Wales and SW England by a multi-source ascertainment strategy. Clinical records were scrutinised and patients interviewed according to a standardized proforma to confirm demographic details including dates of clinical events and therapeutic interventions. Detailed neurological examination including disability assessment was undertaken and patients entered into a structured prospective clinical study. Results: 36 patients were identified fulfilling established criteria for NMO or NMO spectrum disorders, 31(86%) were anti-AQP4 positive, 3(8%) were non-Caucasian. F : M ratio was 9 : 1, median age at onset 38.1 years (range 4–77), mean disease duration 9 years (SD=9.2), and a mean annual relapse rate 0.84 (SD=0.62). Clinical presentation was heterogeneous: optic neuritis (34%), transverse myelitis (59%), brainstem syndrome (6%). Median delay from onset to EDSS 4 was 7 years. 79% had received long-term immunosuppressive therapy with the use of 10 different therapeutic interventions. Conclusion: This study provides data on the disease course, relapse rate and disability accrual in NMO in a cohort of 36 patients. Our data suggest a high variability of treatment regimes. After analysis and consultation with other UK groups we propose a unified treatment algorithm for management of patients with this disorder.